Morphometric assessment of the stylohyoid complex by multislice computed tomography - Hernández-Díaz, Mariana Raquel (2021)
Objective: tomography (MCT). Materials and methods: This was a descriptive, retrospective cross-sectional study. The sample was made up of 238 MCT studies performed in patients of both sexes between 20 to 87 years of age, with indication of tomography of the craniofacial complex. The length of the SHC was measured in lateral views of 3D volumetric reconstructions. The distribution of these cases was obtained according to age, sex, laterality, type, and the reason for the examination. Results: The mean length of the SHC was 30.66 ± 10.58 mm. Of the total sample, 127 (53.4%) individuals showed an elongated SHC; of these, 63.8% were women and 64.6% of the patients presented a bilateral compromise of the complex. Most of the subjects with an elongated SHC were between 30 and 59 years old. The type of ossification most frequently found was type I (continuous elongation). Regarding the reason for the examination, most of the individuals were referred for study of the temporomandibular joint. Conclusions: MCT is a useful tool for the identification and morphometric study of ossification of the SHC, both in length and type. Examination of an ossified SHC is important for the differential diagnosis of cervico-facial pain and temporomandibular joint dysfunction.